Pengaruh Sikap, Self Efficacy, dan Karakteristik Kewirausahaan Terhadap Intensi Berwirausaha (Studi Kasus pada Siswa Kelas XII SMK IT Al Junaediyah) - Dermawan, Safna Mutia; Saori, Sopyan; Nurmala, Resa (Ekonomis: Journal of Economics and Business, 2026)
This study aims to determine the influence of attitudes, self-efficacy, and entrepreneurial characteristics on entrepreneurial intentions using a quantitative approach with descriptive and associative methods. The sample used in this study consisted of 144 students of grade XII of SMK IT Al Junaediyah, using a saturated sampling method. Multiple regression analysis was the technique used in this study. The results showed that attitudes, self-efficacy, and entrepreneurial characteristics have a simultaneous and partial influence on entrepreneurial intentions in grade XII students of SMK IT Al Junaediyah.